Coaction vs. Reciprocal Cooperation Among Unrelated Individuals in Social Cichlids - Taborsky, Michael; Riebli, Thomas (Frontiers in Ecology and Evolution, 2020)
Members of social groups often temporally coordinate their behaviors, for instance in defense or foraging. In the context of cooperation, simultaneous or sequential coordination of behavior may allow social partners to adjust their cooperative effort quickly among each other. By manipulating individual behaviors, here we tested experimentally whether unrelated brood care helpers of the cichlid fish Neolamprologus pulcher would cooperate in dyads when enabled to dig out a joint shelter or to defend their territory against a predator. Both the digging and defense efforts of social partners were contingent on each other's investment, and the test subjects temporally coordinated these behaviors. Remarkably, the direction of conditional responses to each other's cooperative investment diverged between the two chosen experimental time frames, which tested for coaction and reciprocity. Test subjects reduced their own digging and defense efforts while their partners were showing these behaviors themselves, implying that they did not exert coaction but rather economized on their investment. In contrast, if a social partner had helped to dig out the common shelter in a previous time period, focal test fish advanced their digging effort in the subsequent experimental phase, which indicates reciprocal cooperation. Social partners also coordinated shelter use when they could see each other, especially after they had been visually exposed to a predator. Our results reveal coordination of cooperative behaviors among unrelated social partners, which has not yet been experimentally demonstrated in cooperatively breeding vertebrates.